Effects of direct oral anticoagulants on lupus anticoagulant assays in a real-life setting - Antovic, Aleksandra; Norberg, Eva-Marie; Berndtsson, Maria; Rasmuson, Agnes; Malmström, Rickard E.; Skeppholm, Mika; Antovic, Jovan (Thrombosis and Haemostasis, 2017)
Laboratory diagnosis of lupus anticoagulant (LA) is based on prolongation in at least one coagulation assay (diluted Russell’s viper venom time – dRVVT or activated partial thromboplastin time – aPTT), which normalises after addition of phospholipids. Both assays may be influenced by anticoagulants and therefore LA should not be tested during warfarin or heparin treatment. It has been shown (primarily in vitro) that direct oral anticoagulants (DOACs – dabigatran [DAB], rivaroxaban [RIV] and apixaban [API]) may also influence LA testing. We tested the effects of DOACs on assays routinely used for the diagnosis of LA in patients treated with these drugs in a real-life setting. Plasma from patients with atrial fibrillation treated with DAB (n=30), RIV (n=20) and API (n=17) and not known to have LA were tested using dRVVT (LA-screen and LA-confirm, Life Diagnostics) and aPTT (PTT-LA, Diagnostica Stago and aPTT Actin FS, Siemens Healthcare Diagnostics) assays. According to the diagnostics algorithm, dRVVT and aPTT ratios of <1.2 were considered negative, ratios of >1.4 positive, while if the ratios were 1.2–1.4 LA could not be ruled out. Plasma concentrations varied between 8–172 µg/l for DAB, 8–437 µg/l for RIV and 36–178 µg/l for API. LA diagnosis was negative in only eight (27 %) plasma samples from patients treated with DAB, and in five (25 %) and four samples (24 %) from patients treated with RIV and API, respectively. LA Positivity (dRVVT and aPTT ratios >1.4) was found in 5 cases (17 %) among patients treated with DAB, in 10 cases (50 %) treated with RIV and in 7 cases (41 %) treated with API. A concentration-dependent effect of DOACs on dRVVT-based parameters was observed, particularly as regards DAB. At lower concentrations, RIV and API had only minor effects on the confirmatory tests (below 100 µg/l and 70 µg/l, respectively). Our results suggest that a risk of overestimation of LA detection is present in samples from patients treated with DOACs. Therefore, LA testing should not be performed during treatment with DOACs. Prolongation in confirmatory assays may be helpful for the recognition of false positivity, especially as regards DAB.
Keywords: Direct oral anticoagulants; lupus anticoagulant; laboratory assays